Преобразуйте выражение:

а) (2х-5)^2= б)(3а+1\2b)=

в)(а+4b)(2х+1\2а2)=

г)(2х – 1\2 а^2)(2х+1\2а^2)=

Разложите на множители:

б)4а^2+20ab+25b^2

в)4а^2^b2-25x^4

Вычислите, используя формулы сокращённого умножения: а)212______________________

б)19*21____________________

в)482-472___________________

г)1412-2*141*41+412__________

1

Ответы и объяснения

2013-04-14T09:08:40+00:00

а) (2х-5)^2=2x^2-20x+25

б)(3а+1\2b)=0.5(6a+b)

в)(а+4b)(2х+1\2а2)=2ax+8bx+0.5a^3+2a^2b=(2ax+0.5a^3)+(8bx+2a^2b)=0.5a(4x+a^2)+2b(4x+a^2)=(0.5a+2b)(4x+a^2)

г)(2х – 1\2 а^2)(2х+1\2а^2)=4x^2-0.25a^4=0.25(16x^2-a^4)

Разложите на множители:

б)4а^2+20ab+25b^2=(2a+5b)^2=

в)4а^2*b^2-25x^4=(2ab+5x^2)(2ab-5x^2)

Вычислите, используя формулы сокращённого умножения:

а)212

б)19*21=399

в)482-472=10

г)141^2-2*141*41+41^2=(141-41)^2=100^2=10000